2020
DOI: 10.1111/aogs.13972
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of transvaginal cervical cerclage in women at risk of preterm birth following previous emergency cesarean section

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…It would be expected that this intervention would prolong the gestational age at delivery, however, we show that over 70% of these women still deliver preterm despite this intervention, compared with only a quarter in our control group. This is consistent with previous published data from our group showing that transvaginal cerclage is less effective at preventing preterm birth in women who have a sPTB after previous EmCS compared with other high risk women [7].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It would be expected that this intervention would prolong the gestational age at delivery, however, we show that over 70% of these women still deliver preterm despite this intervention, compared with only a quarter in our control group. This is consistent with previous published data from our group showing that transvaginal cerclage is less effective at preventing preterm birth in women who have a sPTB after previous EmCS compared with other high risk women [7].…”
Section: Discussionsupporting
confidence: 93%
“…after 37 week's gestation) SS-EmCS was 3 times the risk of that following an initial term vaginal delivery [3]. We have also recently demonstrated that women receiving cervical cerclage have a 10-fold increased risk of recurrent, early preterm birth < 30 weeks' gestation, even if the emergency caesarean is performed earlier in labour [7]. It has been postulated that unintentional cervical trauma; either by an inadvertently low uterine incision that includes the cervix or caudal extensions into the cervix during the caesarean section, contributes to a compromise in cervical integrity which predisposes to subsequent preterm birth [8,9].…”
Section: Introductionmentioning
confidence: 92%
“…This study has also shown that approximately half of women in the prior term birth group still deliver preterm despite a cervical cerclage, compared with only 20% in our sPTB only group although these numbers are small. This is consistent with previous published data showing that transvaginal cerclage is less effective at preventing PTB in women who have a sPTB after previous term EmCS compared with other high‐risk women 12 …”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous published data showing that transvaginal cerclage is less effective at preventing PTB in women who have a sPTB after previous term EmCS compared with other high-risk women. 12 Although our data suggest a causative link between a prior term birth and subsequent recurrent sPTB, prospective confirmation would be important and is the subject of ongoing investigation. 21 It is also possible that some women may have acquired new risk F I G U R E 1 Gestational age at birth among the three groups (term CS + sPTB, term VB + sPTB and sPTB only groups) (A).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation